Penyuluhan Keselamatan Berkendaraan ( Safety Riding) di Desa Kunir Kecamatan Mbutuh Kapupaten Purworjo - Widiyatmoko; Mike Elly Anitasari; Arif Susanto (Institut Teknologi dan Bisnis Semarang, 2023)
The aim of safety riding outreach activities aims to provide knowledge and information about riding safety to the public so as to increase motorists' awareness of all the possibilities that may occur while riding. The stages of implementing activities are: 1) Analysis of program needs, 2) Activity planning, which is carried out in coordination with local residents. Everything is done by making a schedule to make it easier to carry out subsequent activities, 3) Carrying out activities by presenting safety riding material about riding safely and comfortably. Based on the results that have been carried out from planning, implementation to evaluation, it can be stated that community service activities are running well. From the results of the participant questionnaire, it was stated: 1) Implementation of activity programs with a percentage of 92 percent, 2) Mastery of resource material with a percentage score of 95 percent, 3) Usefulness of the material or program with a score of 89 percent, and 4) Participant satisfaction with a score percentage of 90 percent. This shows that the activity went very well and satisfied the participant